Locomotion Laboratory - Institute of Sport Science - Friedrich Schiller University of Jena (2009)
The Locomotion Lab is equipped with an instrumented treadmill with overhead gantry and safety harness. It also features two in-floor pits to accommodate force platforms. Pulleys and rubber tubes provide optional horizontal force application. Managing Director: Margrit Schaarschmidt